Water imbibition and water sealing in water-driven gas reservoirs development. Issue 1 (January 2023) - Xu, Xuan; Li, Jiangtao; Xu, Yi; Liu, Junfeng; Hu, Yong; Jiao, Chunyan; Guo, Changmin
To improve the poor understanding of the mechanism of spontaneous water imbibition in water invasion in gas reservoirs and overcome the difficulty in quantifying imbibed water and its impact on reservoir development, a study is carried out based on development simulation experiments and theoretical analysis of fluid mechanics. Spontaneous water imbibition is an important mechanical mechanism for the formation of a water seal zone in a low-permeability matrix through water invasion in gas reservoirs. Water imbibition experiments into the reservoir were carried out to clarify the trends of the imbibed distance and imbibed fluid volume to establish the theoretical model of imbibition and to make experimental corrections. An application study was performed based on the understanding of water imbibition and water sealing mechanisms and the building of an imbibition model. The water seal zones formed by imbibition during exploitation are predicted, and the seal-breaking pressure and influx of imbibed water in the water seal zone are evaluated. The research findings fully revealed the large impact of water imbibition on the development of water-driven gas reservoirs, providing technical support for the assessment of water sealing and the establishment of water control measures in water-driven gas reservoirs.